Self-assessment of the teaching - learning factor in the obstetrics faculty under the Coneau model - UNHEVAL - 2010 - Maque Ponce, Mary (2017)
Type of applied research, causal comparative descriptive level because retro prospective study resulted in an analysis that occurs between two variables, conducted in the period January to December 2010. Self-assess the factor 2. Education - learning, applying the model CONEAU (PERU) and create improvement plans within the Department of Obstetrics - UNHEVAL was the aim of this study. The sample was represented by 225 students from second to fifth year, 300 graduates, race officials, 23 teachers and 2 administrative. The instruments were surveys, interviews and checklists. The main conclusions were: 2.1 Draft criteria for the education - Curriculum the value obtained in relation to achieving ideal is 0.7(B)  which represents a very satisfactory performance improvement actions required in the medium and long term. 2.2 Strategies for the approach of teaching - learning the value obtained in relation to achieving ideal is 0.4 (c) , representing an acceptable compliance. For criterion 2.3 Development of learning activities - learning the value obtained in relation to achieving ideal is 0.7 (B) which represents a very satisfactory performance. 2.4 Evaluation criteria for learning and improvement actions the value obtained in relation to achieving ideal is 0.7 (c) which represents a satisfactory compliance and for students and graduates approach the 2.5 value obtained in relation to achieving the ideal is 0.6 (B)  which represents a compliance standard that requires medium-term actions.